Using dyadic observation to explore equitable learning opportunities in classroom instruction - Alyson L. Lavigne; Thomas L. Good (Education Policy Analysis Archives, 2021)
Because of poverty, many children do not receive adequate prenatal care, nutrition, or early childhood education. These inequities combine to ensure that many students enter school with considerably less academic content knowledge and skills for learning than their peers. Teachers and schools did not create these gaps, but they must address them. The impact of schools in reducing gaps has been explored for decades only to yield inconsistent findings. One possible reason for these contradictory results is because these studies ignore classroom process. We argue for the inclusion of process in research on opportunity and achievement gaps to better articulate if schools provide inequitable learning opportunities. Further, we argue for dyadic (teacher to individual student) measurement of classroom process because commonly-used observation instruments only measure teachers’ interactions with the whole class. These instruments obscure differential teacher treatment that may exist in some classrooms. To improve policy and practice, we call for supplementing extant measures of teachers’ whole-class interactions (process) and student outcome (product) measures with those that measure dyadic interactions to learn how opportunities to learn in classrooms and schools are distributed among students to reduce, sustain, or enhance learning gaps.